Peach brown rot control and the relationship of latent infection with postharvest disease - Pivotto Pavanello, Elizandra; Pasquetti Berghett, Magno Roberto; Schultz, Erani Eliseu; Thewes, Fabio Rodrigo; Prediger Schmid, Suele Fernanda; Brackmann, Auri (Revista Ceres, 2025)
The peach brown rot, caused by Monilinia fructicola, is the main disease of the crop, causing significant losses during preharvest and postharvest. This study aimed to evaluate the performance of preharvest fungicide application on brown rot control and verify the role of latent infection and external contamination in postharvest disease. An experiment was carried out in the years 2014 and 2015 in order to evaluate the performance of six active ingredients (captan, iprodione, iminoctadine, tebuconazole, difenoconazole and azoxystrobin) during preharvest on brown rot control and the effect on latent infection. A second experiment was carried out to monitor the latent infection during growth and ripening of the fruit and in order to correlate it with the postharvest disease incidence. The data were submitted to analysis of variance (Anova) and the means were grouped by the Scott-Knott test (p < 0.05), using statistical software Sisvar. The active ingredients iprodione, tebuconazole and difenoconazole were the most efficient in controlling brown rot on the field, while iminoctadine has higher efficiency during postharvest control, acting on latent infections. The incidence of latent infections during fruit growth and ripening has a positive correlation with brown rot incidence at postharvest. The highest disease incidence after storage is due to the latent infections manifestation. Effective chemical control in the field, throughout the growing and ripening of fruit, is an important approach to postharvest brown rot control, even after cold storage and during shelf life at 20 °C.